2020
DOI: 10.1016/j.annonc.2020.08.1498
|View full text |Cite
|
Sign up to set email alerts
|

1851P The added value of the H2 blocker ranitidine in premedication regimens during paclitaxel treatment

Abstract: was overall survival (OS). Survival was estimated by KaplaneMeier method, and comparisons performed with log-rank test.Results: A total of 167 pts were included: median age was 55 years (18À81), 55.7% were females, 91% had an ECOG-PS !2, 75.4% had gastrointestinal primary tumors, and 70.1% had no previous systemic treatment. Median time from cancer diagnosis to MBO was 16 weeks (0-972.4), and median length of hospitalization after CTX was 2 weeks (0.1-13.6). Overall, a total of 159 deaths were observed, with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Other regulatory bodies also recommended alternative treatment options, including oral H2RAs 20,21 . Small-scale studies found that ranitidine may have limited value as a paclitaxel HSR prophylactic agent 22,23 , but H2RA premedication remains part of the product license requirement for paclitaxel 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…Other regulatory bodies also recommended alternative treatment options, including oral H2RAs 20,21 . Small-scale studies found that ranitidine may have limited value as a paclitaxel HSR prophylactic agent 22,23 , but H2RA premedication remains part of the product license requirement for paclitaxel 18,19 .…”
Section: Introductionmentioning
confidence: 99%